Strategy beyond markets - De Figueiredo, John M.; Lenox, Michael; Oberholzer-Gee, Felix; Vanden Bergh, Richard G.; Emerald eBooks (Bingley, U.K. : Emerald, 2016)
Strategy Beyond Markets examines how the strategies employed by firms affect long run value. Scholars in this field focus their attention on firm interactions with entities other than the firm's primary market stakeholders. These stakeholders include international NGOs, environmental groups, local communities, regulators, politicians and the courts. This book is organized around three themes: Public politics, private politics, and integrated political strategy. In public politics, firms use sophisticated instruments (e.g., campaign funding, committee participation) to influence local, national, and international political environments. In private politics, firms work closely with NGOs and other special interest groups to preempt unfavorable policy, react swiftly to crises, and proactively develop socially responsible strategies. Additionally, firms that are heavily influenced by politics are more likely to craft integrated political strategy as part of a more comprehensive plan. This special issue comprises papers from preeminent scholars including David Baron, Jean-Philippe Bonardi, Daniel Diermeier, Thomas Lyon, John Maxwell, Ken Shotts, and Dennis Yao.
Strategy beyond markets: a step back and a look forward / David P. Baron -- Political risk as a hold-up problem: implications for integrated strategy / Kenneth W. Shotts -- Incorporating legislative effectiveness into nonmarket strategy: the case of financial services reform and the Great Recession / Craig Volden, Alan E. Wiseman -- A unified model of political risk / Benjamin A. T. Graham, Noel P. Johnston, Allison F. Kingsley -- Motivations for corporate political activity / Adam Fremeth, Brian Kelleher Richter, Brandon Schaufele -- The market for legislative influence over regulatory policy / Rui J. P. de Figueiredo, Jr., Geoff Edwards -- Corporate reputational dynamics, private regulation, and activist pressure / Jose Miguel Abito, David Besanko, Daniel Diermeier -- Self-regulation and regulatory discretion: why firms may be reluctant to signal green / Thomas P. Lyon, John W. Maxwell -- Private politics daily: what makes firms the target of internet/media criticism? An empirical investigation of firm, industry and institutional factors / Dominik Breitinger, Jean-Philippe Bonardi -- Navigating natural monopolies: market strategy and non-market challenges in radio and television audience measurement markets / Hillary Greene, Dennis A. Yao -- The organization of nonmarket strategy / Dylan Minor -- Complementarity in firms market and political capabilities: an integrated theoretical perspective / Nan Jia, Kyle Mayer -- How patent strategy affects the timing and method of patent litigation resolution / Deepak Somaya.
Includes bibliographical references.
Keywords: Business & Economics -- Strategic Planning; Business strategy; Business planning; Strategic planning; Organizational behavior; Electronic books